The larva of Progomphus lambertoi Novelo-Gutiérrez, 2007 (Odonata: Gomphidae) - Novelo-Gutiérrez, Rodolfo; Gómez-Anaya, José Antonio (Zootaxa, 2011)
The larva of Progomphus lambertoi is described and illustrated; it belongs to the obscurus-group of Progomphus. It appears closely related to P. belyshevi Belle and P. borealis McLachlan based on stature and size of abdominal dorsal protuberances but is easily separated from these species by abdominal color pattern.